Performance of Employees in Agriculture and Plantation Agency of Aceh - Em Yusuf Iis; Armanu Thayib; Mukhlis M. Yunus; Muhammad Adam; Hijzir Sofyan (LPPM Universitas Terbuka, 2024)
Purpose – The objective of this study is examining the influence of organizational culture, work discipline, as well as self-esteem on employee performance in Agriculture and Plantation Agency in Aceh, with work motivation as a mediating variable. Methodology – Census sampling method is used to obtain a total of 380 employees as the respondents and the data analysis is conducted through Structural Equation Model (SEM). Findings – The results show that organizational culture, work discipline, self-esteem, knowledge management, and knowledge management, significantly influence work motivation. Organizational culture, self-esteem, and work motivation, significantly influence employee performance while work discipline does not affect the variable. Organizational culture partially influences mediation toward employee performance with intervening variable of work motivation. However, work motivation does not qualify as a mediation between work discipline as well as employee performance. Self-esteem and knowledge management partially influence mediation on the variable with intervening variable of work motivation. Originality – Organizational culture on employee performance is utilized in this study.